LEVERAGE, EARNING PER SHARE AND PROFITABILITY: A STUDY ON INFRASTRUCTURE COMPANIES LISTED AT IDX FROM YEAR 2015-2018 - James Benjamin Soeindoen; Harlyn Lindon Siagian (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
To measure company performance, use financial ratio analysis to find out several aspects that determine the financial position and company development, one of which is profitability ratios. This study aims to determine the effect of leverage and earnings per share on profitability. The variable leverage (DER) and earnings per share (EPS) as independent variables (independent) and profitability (ROE) as independent variables (dependent). The number of samples used in this study was 48 there are infrastructure companies in the energy sub-sector (6), toll roads, airports, ports, and the like (5), and telecommunications (8) registered on the IDX, the company provides financial reports and annual reports in 2015-2018. Data were collected using a purposive sampling method based on certain conditions. The method in this study uses a non-participant observation method or used secondary data. Data were analyzed using linear regression models. The results show that leverage does not oppose profitability, while earnings per share tend to profitability.